Duration of Mejejaitan and the Risk of De Quervain's Tenosynovitis Among Banten Artisans in Gianyar Regency - Wona, Yohana Virani; Saraswati, Ni Luh Putu Gita Karunia; Sugiritama, I Wayan; Andayani, Ni Luh Nopi (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : Religious rituals in Balinese Hinduism involve numerous ceremonies with offerings called banten. An essential stage in making Banten is mejejaitan, where artisans use staplers instead of bamboo skewers in crafting. However, prolonged use of staplers and highly repetitive behaviour can increase the risk of de Quervain's tenosynovitis. This study aims to determine the relationship between the duration of mejejaitan and the risk of developing de Quervain's tenosynovitis among Banten artisans in Gianyar Regency. Methods : This observational study used a cross-sectional approach, with purposive sampling yielding 88 subjects. The independent variable was the duration of mejejaitan, while the dependent variable was de Quervain's tenosynovitis. Data collection was conducted through direct interviews to gather information about the duration of mejejaitan. Additionally, specific tests such as the WHAT test were performed to assess the risk of de Quervain's tenosynovitis, and pain intensity was measured using the NRS. Results : Data analysis using the Spearman rho test yielded a p-value of 0.018, indicating a relationship between the duration of mejejaitan and the risk of de Quervain's tenosynovitis. The correlation coefficient r of 0.251 showed a positive correlation, suggesting a direct relationship with a low correlation strength. Conclusion : The longer the duration of mejejaitan without rest, the higher the risk of developing de Quervain's tenosynovitis.   Keywords : de Quervain's tenosynovitis, mejejaitan, Banten artisans